(untitled) (Journal of the College of Basic Education, 2020)
The Russian policy aimed at ensuring energy security to export it to consuming countries at all times in sufficient quantities and at reasonable prices, to benefit from its political and economic dimensions has included a number of measures, including the continuity of establishing strategic projects for energy transfer and addressing the American-European project (Nabucco), as well as stopping The Southern Stream running through Ukraine to European countries, and supporting the role of oil partnerships to implement major projects to transfer energy. However, Russian policy faces major challenges such as the establishment of a Western country’s power transmission projects to compete with Russia in this area. In light of the interests of different and often intersecting countries, the process of ensuring energy security becomes the biggest challenge for exporting and importing countries. In addition to the long distances in which the power transmission lines extend between the producing and consuming countries, which need great capabilities to implement and protect them within the conclusion of agreements with the corridor countries to allow the use of their lands. The use of energy-efficient economic ingredients in Russia’s foreign policy will lead to the development of its relations with countries importing Russian energy, Such as European Union countries as well as China and Turkey. The Russian foreign activities and endeavors have expanded to include deepening its relations with the countries of Central Asia, the Caucasus and the Arab Gulf states that join the Organization of Petroleum Exporting Countries (OPEC) alongside Venezuela, which is one of the major oil producers in South America.